Comparative study of chronic energy deficiency among adult males of Andaman and Nicobar Islands and their counterparts - Sahani Ramesh; Gautam Rajesh K.; Golnabi Amir H.; Vedwan Neeraj (Anthropological Review, 2018)
The indigenous islanders of Andaman and Nicobar Islands are representing the earliest form of developmental stage, their nutritional assessment and anthropometric comparison with contemporary populations are the main objective of the present paper. In this study we present a cross sectional analysis of anthropometric data of 2010 individuals of 19 different groups. The data were collected by the trained anthropologists of Anthropological Survey of India, following standard techniques and ethical guidelines. It was found that the Indigenous Islanders have small body size as compared to immigrants and counterparts. The prevalence of chronic energy deficiency (CED) was found highest among the mainlanders. Highest prevalence of overweight was found among Great Andamanese (18.2%), followed by Onge (7.4%). Individuals below 21 years of age were not found to be overweight or obese. On the other side, 16.7% of individual of age 41+ of local born were found to be overweight (BMI 25.0-29.9 kg/m2). It can be concluded that the Indigenous people of the Islands are short in stature and nutritionally better than immigrants. The immigrants are better than their counterparts in the mainland, but still they are not able to reach at par of the indigenous people in the level of nutrition whereas logarithmic transformation of data and scaling exponent (β) of weight to height was found ~2 across these populations.